2011
DOI: 10.5137/1019-5149.jtn.3901-10.0
|View full text |Cite
|
Sign up to set email alerts
|

Primary amenorrhea due to empty sella: an underestimated entity

Abstract: We report a 16-year-old girl who had stunted growth and primary amenorrhea presenting with headache and vomiting. MRI of brain showed posterior fossa dermoid cyst with hydrocephalus and empty sella. Growth hormone (GH), Leutinizing hormone (LH) and Follicular stimulating hormone (FSH) were grossly reduced on endocrinological work-up. She underwent suboccipital midline craniectomy and complete excision of dermoid cyst .She had no additional deficit after the surgery. She had menarche six months after the surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Related to intracranial hypertension, 10% of these patients were referred to hospital with headache and visual-field defects [ 23 ]. Data from autopsy series and neuroradiological studies reported that primary empty sella accounted for about 5.5% to 35% of those subjects, and it was observed four times frequently in women [ 24 , 25 ]. The peak incidence of PES occurred between the third and fourth decades [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Related to intracranial hypertension, 10% of these patients were referred to hospital with headache and visual-field defects [ 23 ]. Data from autopsy series and neuroradiological studies reported that primary empty sella accounted for about 5.5% to 35% of those subjects, and it was observed four times frequently in women [ 24 , 25 ]. The peak incidence of PES occurred between the third and fourth decades [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed laboratory investigations and imaging revealed empty sella syndrome as a cause of their clinical presentations. 7,8 Severe hyponatremia as a manifestation of empty sella syndrome is rare. Severe hyponatremia along with low blood pressure and nausea should raise the possibility of abnormality in pituitary hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Dange et al[11] reported a 16-year-old girl with a history of stunted growth and primary amenorrhea, presenting with headache and vomiting. Endocrine testing showed reduced levels of growth hormone, luteinising hormone, and follicular stimulating hormone.…”
Section: Discussionmentioning
confidence: 99%